2019
DOI: 10.1371/journal.pone.0218543
|View full text |Cite
|
Sign up to set email alerts
|

Anti-obesity effects of Spirulina platensis protein hydrolysate by modulating brain-liver axis in high-fat diet fed mice

Abstract: Spirulina platensis is a blue-green algae with potential anti-obesity effects. In this study, the anti-obesity effects of whole Spirulina platensis (WSP), Spirulina platensis protein (SPP) and Spirulina platensis protein hydrolysate (SPPH) were compared in high-fat diet fed mice, and the potential acting mechanism of SPPH was also investigated. Totally, SPPH exhibited good anti-obesity effects (reducing 39.8%±9.7% of body weight), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 43 publications
(41 reference statements)
3
28
0
1
Order By: Relevance
“…The antioxidant compounds in spirulina, such as phycobilins and phycocyanins, also inhibit the activities of catalytic enzymes, such as lipoxygenase and cyclooxygenase, or enhance the activity of enzymes, such as glutathione peroxidase, catalase, and superoxide dismutase [59,60]. These polyphenols were reported to have anti-inflammatory, antiviral, antioxidant, antithrombotic, vasodilatory, antidiabetic, neuroprotective, hepatoprotective, and anticarcinogenic properties [21,22,24,28,29,32,[35][36][37][59][60][61][62][63]. However, the metabolic pathways for the formation of phenolic compounds in spirulina and their importance are still unknown [64].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant compounds in spirulina, such as phycobilins and phycocyanins, also inhibit the activities of catalytic enzymes, such as lipoxygenase and cyclooxygenase, or enhance the activity of enzymes, such as glutathione peroxidase, catalase, and superoxide dismutase [59,60]. These polyphenols were reported to have anti-inflammatory, antiviral, antioxidant, antithrombotic, vasodilatory, antidiabetic, neuroprotective, hepatoprotective, and anticarcinogenic properties [21,22,24,28,29,32,[35][36][37][59][60][61][62][63]. However, the metabolic pathways for the formation of phenolic compounds in spirulina and their importance are still unknown [64].…”
Section: Discussionmentioning
confidence: 99%
“…It has a high content of total phenolic compounds such as catechin hydrate, epicatechin, pyrocatechol, C-phycocyanin and β-carotene, which contribute to the major antioxidant activity of spirulina. The phenolic compounds present in spirulina are primarily involved in the redox mechanism and function to prevent the formation of reactive oxygen species (ROS), eventually inhibiting inflammatory responses via anti-oxidative and anti-inflammatory mechanisms that have protective effects against various human diseases such as mild chronic inflammatory disease [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the levels of ALT, AST, ALP, and albumin were significantly different between the group IIb and group IIa. Treatment with Spirulina is reported to significantly decrease the levels of cholesterol, serum triacylglycerol, and LDL-C and to significantly increase the levels of HDL-C (El-Sheekh et al 2014;Zhao et al 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Spirulina is a potential therapeutic agent for hepatotoxicity caused by oxidative stress and the antioxidative potential of Spirulina was related to its phycocyanin component (Hussein et al 2015). Recent clinical trials showed promising effects of Spirulina for reducing body weight in obese humans (Moradi et al 2019) and mice (Zhao et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The role of spirulina on body weight control is not fully elucidated yet. In murine models, spirulina extracts administration showed anti-obesity and lipids-lowering effects [128,129], mediated by different mechanisms, such as adipogenesis suppression, browning of white adipose tissue [129], and modification in brain and liver genes expression [128]. In humans, it proved effective in decreasing appetite [130].…”
Section: Spirulinamentioning
confidence: 99%